ULTRA PETITA DALAM PENGUJIAN UNDANG-UNDANG DAN JALAN MENCAPAI KEADILAN KONSTITUSIONAL - Chandranegara, Ibnu Sina (Mahkamah Konstitusi Republik Indonesia, 2012)
The existence of Constitutional Court after the amendment the 1945 Constitution of Republic Indonesia (1999-2002) brought a fundamental change in the constitutional review of norms. Constitutional review mechanism not just a “review” but the court is also required to search the essence of constitutional review itself and its relation to the constitutional rights. Therefore, the ultra petita decisions issued by the Court should not be viewed as absurd but as a way to uphold justice.